ACTIVITIES OF THE UKRAINIAN DIASPORA IN THE HIGHLIGHTING OF THE HOLODOMOR OF 1932-33 - HOMOTIUK, Oksana; NEDOSHYTKO, Iryna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The proposed article considers the educational activities of the Ukrainian diaspora in the United States. It was found that the education system of Ukrainian communities at the present stage continues to develop. There are parish schools at Catholic churches with full-time education, founded in the 80s of the XX century, they are Ukrainian in name, and in content - mostly American. It has been determined that Ukrainian Saturday schools under the direction of the US School Board under the Ukrainian Congressional Committee of America function most effectively, although their number is not sufficient according to the Ukrainian population.